Pemanfaatan Linktree, Google Form, Youtube dan Quizizz Sebagai Media Bantu Pembelajaran Daring selama Periode Adaptasi Baru di SDN Dayeuhkolot II Subang - Rina Kurniawati; Syifaul Fuada; Febri Dawani (Universitas Pendidikan Indonesia Kampus Purwakarta, 2021)
SDN Dayeuhkolot II is one of the public elementary schools in Subang Regency, West Java province. During the new adaptation period, the teaching and learning activities were conducted online. However, the teaching and learning process has not been optimal because schools and students are not fully ready to conduct online learning. Therefore, we found some obstacles during the teaching and learning activities. To accomplish this problem, an online learning strengthening program has to be implemented in SDN Dayeuhkolot II, Subang. The program was applied only to grade IV and V students from November 17 to December 4, 2020. The implementation method consisted of planning, the main program, and evaluation. Online learning took advantage of freely available tools and was easy to operate, namely Linktree and Quizizz. Linktree served as a medium for linking links related to teaching materials, including links for access to Youtube (videos containing learning materials) and links to Google forms (student attendance, test results from programs, testimonials). The Quizizz was used as an online evaluation. This strengthening program results showed that students gave an excellent response to the use of online learning media. They are comfortable carrying out online learning through the use of Linktree and Quizizz media.